Hubungan Pengetahuan dan Sikap Terhadap Perilaku Pacaran Berisiko pada Remaja di SMK PGRI 16 Jakarta Tahun 2025 - Nani Aisyiyah; Dewi Nawang Sari; Della Eriani Akaputri; Lina Herlina; Santi Agustina; Ari Waluyo; Ismail Sangadji (JURNAL BIDANG ILMU KESEHATAN, 2026)
Risky dating behavior among adolescents is a reproductive health problem that can lead to unwanted pregnancies, sexually transmitted infections, and psychological and social disorders. Lack of knowledge and negative attitudes among adolescents towards reproductive health are factors that can influence risky dating behavior. The purpose of this study was to determine the relationship between knowledge and attitudes towards risky dating behavior among adolescents at SMK 16 Jakarta in 2025. This type of research used quantitative research with a cross-sectional design. The population in this study were all 300 grade XI students with a sample of 171 respondents taken using systematic random sampling techniques. Data collection was carried out using questionnaires that had been tested for validity and reliability. Data analysis used univariate and bivariate analysis with the chi-square test. The results showed that the majority of respondents had non-risky dating behavior, namely 41 (61.2%), high knowledge of 37 (55.2%), and positive attitudes of 34 (50.7%). The results of the bivariate analysis showed a relationship between knowledge and risky dating behavior with a p-value = 0.000 < 0.05 and OR = 7.4, and there was a relationship between attitude and risky dating behavior with a p-value = 0.000 < 0.05 and OR = 15.0. Adolescents with low knowledge have a 7.4 times greater chance of engaging in risky dating behavior, while adolescents with negative attitudes have a 15 times greater chance than adolescents with positive attitudes. It is recommended that schools and health workers improve adolescent reproductive health education